PENDAMPINGAN PEMBELAJARAN KITAB KUNING METODE AL-MIFTAH UNTUK PENINGKATAN KOMPETENSI SANTRI - Heridianto Heridianto; Muhellah Muhellah; Heridianto Heridianto; Muhellah Muhellah (Mafaza : Jurnal Pengabdian Masyarakat, 2026)
The skill of reading the yellow book is an important ability for students in understanding classical Islamic literature, but many novice students still experience difficulties due to limited mastery of Arabic grammar and less varied learning methods. This service aims to improve the ability to read the yellow book in Nurul Ikhsan students through Al-Miftah learning assistance as a systematic and easy-to-understand basic method. The partners in this activity are beginner students at the Nurul Ikhsan Islamic Boarding School. The service method uses a Participatory Action Research (PAR) approach through face-to-face activities, gradual teaching, memorization exercises, provision of basic nahwu sharaf materials and educational games to facilitate understanding. The results of the service showed an increase in the ability of students to read the yellow book better and more accurately, as well as an increase in motivation to learn through a variety of teaching methods. These findings show that Al-Miftah method based mentoring is effective in helping novice students understand the yellow book and is important to be applied sustainably in the pesantren environment.